PENERAPAN MODEL PROJECT BASED LEARNING UNTUK MENINGKATKAN PARTISIPASI BELAJAR SISWA DI SEKOLAH DASAR - Silfi Ghifari; M. Syahrul Rizal; Rizki Ananda; Zulhendri; Nurhaswinda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was prompted by the low student participation in IPAS (Science, Social Studies, and Arts) learning among fourth-grade students at SD IT Hamalatul Ilmi. The study aimed to increase student learning participation by implementing the Project-Based Learning (PjBL) model in the fourth-grade classroom at SD IT Hamalatul Ilmi Bangkinang.This was a classroom action research project. The subjects of this study were 12 fourth-grade students from SD IT Hamalatul Ilmi. The research cycle followed the stages of planning, implementing, observing, and reflecting. Data collection techniques included documentation and observation. Data analysis techniques used both qualitative and quantitative methods.The results of this study indicate that the Project-Based Learning (PjBL) model can enhance student learning participation. This is evidenced by the improvement in student participation scores. In Cycle I, Meeting I, student participation reached 62,91%, with 5 out of 12 students achieving mastery. This increased to 73,33% in Cycle I, Meeting II, with 6 out of 12 students achieving mastery. Further improvement was observed in Cycle II, Meeting I, reaching 78,75%, with 8 out of 12 students achieving mastery. Finally, in Cycle II, Meeting II, participation increased again to 84,68%, with 10 out of 12 students achieving mastery.Therefore, it can be concluded that implementing the Project-Based Learning model can increase student learning participation at SD IT Hamalatul Ilmi.